Vista de la Facultad de Educación de la Universidad Nacional de la Amazonía Peruana - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1999)
SPANISH: Vista de la Facultad de Educación de la Universidad Nacional de la Amazonía Peruana, con presencia de humo en su techo y una manifestación estudiantil en el exterior.
ENGLISH: View of the Faculty of Education of the National University of the Peruvian Amazon, with smoke on its roof and a student demonstration outside.

SPANISH: Vista de la Facultad de Educación de la Universidad Nacional de la Amazonía Peruana, con presencia de humo en su techo y una manifestación estudiantil en el exterior.
ENGLISH: View of the Faculty of Education of the National University of the Peruvian Amazon, with smoke on its roof and a student demonstration outside.
View of the Faculty of Education of the National University of the Peruvian Amazon
Keywords: Social events|~|Iquitos (Perú)|~|Catholic Institutions|~|Catholic schools|~|Catholic priests|~|Acontecimientos sociales|~|Iquitos (Perú)|~|Instituciones Católicas|~|Escuelas Católicas|~|Sacedote Católica